(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The continuous digital and technical development has led to the transformation of transactions from their traditional reality to the digital and cyberspace. The research problem is that all businesses, transactions and operations are electronic, which exposes them to cyber attacks, and that the professional responsibility of the auditor will be affected by cyber security risks. The main research hypothesis was the existence of a direct relationship between responsibility The professionalism of the auditor and cyber security risks, as the research seeks to know the extent to which the public and private sectors have adopted a cyber-security plan through a program or framework emanating from the Iraqi cyber security strategy (2022-2025) and the conclusions it reached that there is a relationship between the professional responsibility of the auditor The most important of which are cyber security risks, the most important of which is that most financial and banking entities have not identified or disclosed cyber security risks and the absence of a law or binding legal framework, which affects the audit procedures and the opinion of the auditor. This affects the professional responsibility of the auditor, as well as the failure to disclose these risks, which exposes them to threats from by organizing a cyber-security law that is binding on everyone. Opening remarks auditor cyber security